Energy management and DC-bus voltage control for DC microgrids - Ng, Wei Jeak (2018)
With the rapid depletion of fossil fuels, the DC microgrid is gaining attention in power generation to integrate the renewable energy sources. Various control methods have been proposed to Hybrid Energy Storage System (HESS) with renewable energy sources in a stand-alone DC microgrid. A Proportional-Integral (PI) based control approach is introduced to solve the conflict issue on the current controller in HESS. It can also provide fast voltage restoration at DC bus. This is because the voltage error term and the uncompensated power from the battery are diverted into supercapacitor system to accomplish fast voltage restoration at DC bus. A predictive term is used in this approach to control the battery current and supercapacitor current. Moreover, it also reduces the stress in the battery to extend the battery life. The stability analysis and effectiveness of the approach are validated by comparing simulation and hardware-in-loop experiments. The DC microgrid is broken down into several parts and each part is modelled individually in Matlab/Simulink. Each part is tested independently. After that, a complete DC microgrid will then be modelled in Matlab/Simulink and tested by examining the offline simulation result. Upon successful of the offline simulation, the entire model is imported to the OPAL-RT simulator to conduct real-time simulation to show how the system respond in real time. The real-time simulation results are verified with the offline simulation results. Other than that, Hardware-In-Loop (HIL) experiments are also conducted to examine the response of the controller for the system in real time. MicroLabBox acts as a real-time controller for the system and it is incorporated with the OPAL-RT to carry out HIL simulations. The results are compared with the real-time simulation offline simulation results to validate the performance of the system controller in real time.